The Relationship Between Financial Support, Community Participation and Community's Growth Mindset with The Success of Badak LNG's CSR Programs (Journal of Business and Management, 2022)
Abstract. Badak LNG is a non-profit natural gas processing company that actively participates in community service through corporate social responsibility (CSR). Badak LNG swiftly recognizes the importance CSR in promoting and contributing to local community development. The purpose of this study is to identify the relationship between financial support, community participation and community's growth mindset with the success of Badak LNG's corporate social responsibility program. This study takes a quantitative approach with a survey method. 100 samples were obtained using an online questionnaire addressed to residents in the West Bontang District who are familiar with or involved in Badak LNG's CSR program. The study's findings revealed that financial support, community participation, and the community's growth mindset all had impact on the performance of Badak LNG's CSR program. This research can help Badak LNG and other companies to maximize their CSR impact in the community.Keywords: Corporate Social Responsibility, Financial Support, Community Participation, Community’s Growth Mindset